A comprehensive molecular study identified 12 complementation groups with 56 novel FANC gene variants in Indian Fanconi anemia subjects. Issue 12 (5th October 2021) - George, Merin; Solanki, Avani; Chavan, Niranjan; Rajendran, Aruna; Raj, Revathi; Mohan, Sheila; Nemani, Sandeep; Kanvinde, Shailesh; Munirathnam, Deendayalan; Rao, Sudha; Radhakrishnan, Nita; Lashkari, Harsha Prasada; et al.
Abstract: Fanconi anemia (FA) is a rare autosomal or X‐linked genetic disorder characterized by chromosomal breakages, congenital abnormalities, bone marrow failure (BMF), and cancer. There has been a discovery of 22 FANC genes known to be involved in the FA pathway. This wide number of pathway components makes molecular diagnosis challenging for FA. We present here the most comprehensive molecular diagnosis of FA subjects from India. We observed a high frequency (4.42 ± 1.5 breaks/metaphase) of chromosomal breakages in 181 FA subjects. The major clinical abnormalities observed were skin pigmentation (70.2%), short stature (46.4%), and skeletal abnormalities (43.1%), along with a few minor clinical abnormalities. The combination of Sanger sequencing and Next Generation Sequencing could molecularly characterize 164 (90.6%) FA patients and identified 12 different complementation groups [ FANCA (56.10%), FANCG (16.46%), FANCL (12.80%), FANCD2 (4.88%), FANCJ (2.44%), FANCE (1.22%), FANCF (1.22%), FANCI (1.22%), FANCN (1.22%), FANCC (1.22%), FANCD1 (0.61%) and FANCB (0.61%)]. A total of 56 novel variants were identified in our cohort, including a hotspot variant: a deletion of exon 27 in the FANCA gene and a nonsense variant at c.787 C>T in the FANCG gene. Our comprehensive molecular findings can aid in the stratification of molecular investigation in the diagnosis and management of FA patients. Abstract : The combination of Sanger sequencing and Next Generation Sequencing could molecularly characterize 164 (90.6%) FA patients and identified 12 different complementation groups [FANCA (56.10%), FANCG (16.46%), FANCL (12.80%), FANCD2 (4.88%), FANCJ (2.44%), FANCE (1.22%), FANCF (1.22%), FANCI (1.22%), FANCN (1.22%), FANCC (1.22%), FANCD1 (0.61%) and FANCB (0.61%)] including 56 novel variants.